Distribution of CFTR mutations in Eastern Hungarians: relevance to genetic testing and to the introduction of newborn screening for cystic fibrosis - Ivady, Gergely; Madar, Laszlo; Nagy, Bela; Gonczi, Ferenc; Ajzner, Eva; Dzsudzsak, Erika; Dvořáková, Lenka; Gombos, Eva; Kappelmayer, Janos; Macek, Milan; Balogh, Istvan (Journal of cystic fibrosis, 2011)
BACKGROUND: The aim of this study was characterization of an updated distribution of CFTR mutations in a representative cohort of 40 CF patients with the classical form of the disease drawn from Eastern Hungary. Due to the homogeneity of the Hungarian population our data are generally applicable to other regions of the country, including the sizeable diaspora. METHODS: We utilized the recommended "cascade" CFTR mutation screening approach, initially using a commercial assay, followed by examination of the common "Slavic" deletion CFTRdele2,3(21kb). Subsequently, the entire CFTR coding region of the CFTR gene was sequenced in patients with yet unidentified mutations. RESULTS: The Elucigene CF29(Tm) v2 assay detected 81.25% of all CF causing mutations. An addition of the CFTRdele2,3(21kb) increased the mutation detection rate to 86.25%. DNA sequencing enabled us to identify mutations on 79/80 CF alleles. Mutations [CFTRdele2,3(21kb), p.Gln685ThrfsX4 (2184insA) were found at an unusually high frequency, each comprising 5.00% of all CF alleles. CONCLUSION: We have identified common CF causing mutations in the Hungarian population with the most common mutations (p.Phe508del, p.Asn1303Lys, CFTRdele2,3(21kb), 2184insA, p.Gly542X, and p.Leu101X), comprising over 93.75% of all CF alleles. Obtained data are applicable to the improvement of DNA diagnostics in Hungary and beyond, and are the necessary prerequisite for the introduction of a nationwide "two tier" CF newborn screening program.
Keywords: mutace; Cystic Fibrosis Transmembrane Conductance Regulator; Genetic Testing; dítě; novorozenec; mladý dospělý; Neonatal Screening; Adolescent; cystická fibróza; DNA; lidé; Gene Frequency; Infant, Newborn; protein CFTR; Mutation; frekvence genu; kohortové studie; Cohort Studies; Cystic Fibrosis; Young Adult; alely; genetické testování; Hungary; Alleles; Child; novorozenecký screening; Maďarsko; mladiství; Humans